2015
DOI: 10.1080/03004430.2015.1028396
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment through pedagogy: positioning service-learning as an early childhood pedagogy for pre-service teachers

Abstract: Over the past decade early childhood education (ECE) teachers have faced increasing pressures to implement standardised tests in order to secure external validation and funding. In response, many teacher education programmes now focus heavily on positivistic training approaches, as opposed to more developmentally appropriate pedagogies [Winterbottom, C., & Lake, V. E. (2013) Cultivating leadership and responsibility in children. Exchange, 5,[36][37][38][39]. In this study, we examined the effectiveness of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A service-learning educational model is participatory, democratic, and collaborative in nature, and in early childhood is best practiced by those who are committed and close to the real world of young children and their families (Winterbottom & Mazzocco, 2015). This pedagogy is grounded in real world situations, and is carried out by practitioners, in collaboration with the community at large who have a direct and passionate investment in what is occurring inside the classroom; it is largely carried out as collaboration with people in context and not to people (Freire, 1970).…”
Section: How Is Service-learning Practiced?mentioning
confidence: 99%
See 2 more Smart Citations
“…A service-learning educational model is participatory, democratic, and collaborative in nature, and in early childhood is best practiced by those who are committed and close to the real world of young children and their families (Winterbottom & Mazzocco, 2015). This pedagogy is grounded in real world situations, and is carried out by practitioners, in collaboration with the community at large who have a direct and passionate investment in what is occurring inside the classroom; it is largely carried out as collaboration with people in context and not to people (Freire, 1970).…”
Section: How Is Service-learning Practiced?mentioning
confidence: 99%
“…This epistemology is then used to inform teaching and learning, and provides a framework for shaping future learning. To this point, a lot of the evidence that has informed practice has been imposed on the educational field from external sources (Pascal & Bertram, 2012;Winterbottom & Mazzocco, 2015) but using a service-learning approach teachers can potentially advocate change and reform from within outward.…”
Section: Strengths and Limitations Of Service-learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though, wide-ranging academic research has investigated the influence of early childhood pedagogy as one of the most significant drivers of children's development (Gananathan, 2011;Harris, 2015;Farquhar and White, 2014;Hedges and Cullen, 2012;Murray, 2015;Winterbottom and Mazzocco, 2015) much less research has explored early childhood pedagogy and its attendant contribution to children's development in diverse ways within the West-African sub-region. Besides, earlier studies focused on differing sociocultural contexts so these studies are silent regarding the extent to which children's socio-cultural settings influence selection of pedagogy and the significance therein.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that practitioners should be encouraged to be creative in their approach and to embrace change as this is beneficial for children's learning (Fullan, 2001). This is supported further by Winterbottom and Mazzocco (2015) in their study of American early childhood teachers who concluded that a service-learning pedagogical approach where teachers learn by doing and which involves opportunities for teachers to develop self-efficacy and assume responsibility for growth can lead to a more positive approach to learning as opposed to one which is data and assessment driven. In a study of creative teachers, Craft et al (1997) found that self-esteem and self-confidence should be nourished for practitioners to be creative in addition to personal and professional autonomy, the capacity to take risks and the ability to reflect critically on practice which is viewed as flexible and evolving rather than rigid and static.…”
Section: The Role Of the Adult In Supporting Children's Dispositionsmentioning
confidence: 86%